CT-based quality control of Laser Sintering of Polymers. (November 2016) - Pavan, Michele; Craeghs, Tom; Verhelst, Raf; Ducatteeuw, Olivier; Kruth, Jean-Pierre; Dewulf, Wim
Abstract: Laser Sintering (LS) is an Additive Manufacturing (AM) technology for polymers processing which is increasingly being used to produce functional products with designs not achievable with traditional manufacturing technologies. Lightweight cellular structures are a good example of complex designs which are increasingly finding applications in AM parts. However, it is not yet clear how the LS process affects the porosity and geometrical characteristics of the cell structural elements. Getting this information allows to perform quality control of the LS process, gives insights into how to improve it, and might help to take into account manufacturing process variability during the design phase. In this work a test artifact containing cylindrical elements with diameters in the range typically used in lightweight cellular structures is used to investigate the influence of features' size and printing orientation on the porosity and shape deviation of each feature. In order to assess the reproducibility of the process, several replicas of the test object are produced in polyamide-12 (PA12) using the same LS process conditions. An X-ray Computed Tomography (CT)-based quality control approach, which uses both image processing of CT-slices and porosity analysis (porosity content, pores count and pores volume distributions) is used to gather the information.